The Influence Of Perceived Benefits, Ease Of Use, And Farmer Trust On Agricultural Electrification - Agus susilo; Suswadi; Norbertus Citra Irawan (Journal of Rural and Urban Community Studies, 2026)
This research is motivated by the high dependence of rice farmers in Boyolali Regency on diesel-fueled water pumps, which causes high operational costs and production instability due to fluctuations in fuel prices. Agricultural electrification through the use of electric pumps is a more efficient and sustainable alternative, but its adoption rate is still relatively low. This study aims to analyze the influence of Perceived Benefits, Ease of Use, and Farmer Trust on the Adoption of Agricultural Electrification. The study used a quantitative approach with a descriptive-analytical method. The study population was all rice farmers who had used or had access to electric pumps in Giriroto Village, Ngemplak District, and Babadan Village, Sambi District, Boyolali Regency. The study was conducted from December 2025 to January 2026. Primary data were collected through a Likert-scale questionnaire and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results showed that Perceived Benefits and Ease of Use had a positive and significant effect on the Adoption of Agricultural Electrification, while Farmer Trust had no significant effect. An R² value of 0.770 (77%) indicates that the model has strong explanatory power. This finding indicates that adoption decisions are more influenced by tangible benefits and ease of use than by trust. The implications of this research emphasize the importance of strengthening the dissemination of benefits and improving the ease of operation of the technology to accelerate agricultural electrification.